2011
DOI: 10.1007/s11605-010-1360-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 230 Cases of Emergent Surgery for Obstructing Colon Cancer—Lessons Learned

Abstract: All these factors but the timing of the operation emphasize the pivotal role of the patient's physiological condition on admission. Accurate preoperative evaluation might predict the clinical outcome and help in establishing the most appropriate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 26 publications
4
51
2
4
Order By: Relevance
“…All 14 studies reported on mortality rates (Tables 4 and 5) [3,5,[10][11][12][13][14][15][16][17][18][19][20][21]. Mean overall mortality was 10.8 % (8.1-18.5 %) in the primary resection group (n=2873) and 0 % in the stent group (n=155).…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…All 14 studies reported on mortality rates (Tables 4 and 5) [3,5,[10][11][12][13][14][15][16][17][18][19][20][21]. Mean overall mortality was 10.8 % (8.1-18.5 %) in the primary resection group (n=2873) and 0 % in the stent group (n=155).…”
Section: Mortalitymentioning
confidence: 99%
“…(17) 25.6 (7) 30. Morbidity rates could be classified further into major or minor morbidity in 8 of 14 studies [11,14,15,[17][18][19]21], reporting on 535 patients in the primary resection group and 108 in the stent group. Minor morbidity, grade IIIa or lower, was not significantly different for the primary resection group 26.5 % (16.3-51.2 %) compared with the stent group 3.4 % (0-7.1 %) (p=0.77).…”
Section: Mortalitymentioning
confidence: 99%
“…Similarly, Kısaoglu et al showed that ASA3-4 scores were associated with high postoperative morbidity in their patient group, in addition to age above 70 and the presence of accompanying systemic disease [4]. In another study with 230 cases of emergent surgery for obstructing colon carcinoma, analysis revealed that ASA grade ≥3 was one of the most important prognostic factors for poor outcome [12]. Preoperative hemoglobin and albumin values, tumor localization, the type of surgery, tumor stage, and the presence of distant metastasis are also among the reported factors affecting on both postoperative morbidity and mortality of the patients with obstructing CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Однако формирование первичного анастомоза после резекции левых отделов толстой кишки в связи с осложненной перифокаль-ным воспалением опухолью является весьма риско-ванным вследствие плохой подготовки кишки и из-за наличия воспалительного процесса в брюшной поло-сти [6,19,74].…”
Section: Introductionunclassified
“…При локализа-ции опухоли в средней трети поперечной ободочной кишки выполняют ее резекцию по Гартману. В случае расположения опухоли в левых отделах и наличия возможности удаления абсцесса без его вскрытия также рекомендуют проводить резекцию ободочной кишки по Гартману [6,12,25,74]. Если отсутствует возмож-ность удаления опухоли, а также при наличии отдален-ных метастазов проводят пункцию полости абсцесса или его вскрытие и дренирование экстраперитонеально, Онкологическая ONCOLOGY ТОМ 7 / VOL.…”
Section: Introductionunclassified